2023
DOI: 10.1136/military-2022-002326
|View full text |Cite
|
Sign up to set email alerts
|

Victorian Institute of Sport Assessment—Achilles thresholds for minimal important change and return to presymptom activity level in active soldiers with mid-portion Achilles tendinopathy

Abstract: IntroductionMid-portion Achilles tendinopathy (mid-AT) is common in soldiers, significantly impacting activity levels and operational readiness. Currently, Victorian Institute of Sport Assessment—Achilles (VISA-A) represents the gold standard to evaluate pain and function in mid-AT. Our objective was to estimate VISA-A thresholds for minimal important change (MIC) and patient-acceptable symptom state for return to the presymptom activity level (PASS-RTA), in soldiers treated with a conservative programme for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Patients with low SES reported a mean VISA-A score that was 7–11 points lower at 24 weeks compared with patients with high SES. While this difference aligns with or exceeds the minimal clinically important difference of 7 points,40 41 indicating potential clinical relevance, it is important to note that sensitivity analyses of the VISA-A scores only suggest a trend and did not demonstrate statistically significant differences between groups at all time periods, possibly due to the large dispersion of data. This highlights the need for cautious interpretation of these findings.…”
Section: Discussionmentioning
confidence: 52%
“…Patients with low SES reported a mean VISA-A score that was 7–11 points lower at 24 weeks compared with patients with high SES. While this difference aligns with or exceeds the minimal clinically important difference of 7 points,40 41 indicating potential clinical relevance, it is important to note that sensitivity analyses of the VISA-A scores only suggest a trend and did not demonstrate statistically significant differences between groups at all time periods, possibly due to the large dispersion of data. This highlights the need for cautious interpretation of these findings.…”
Section: Discussionmentioning
confidence: 52%
“…Although there was no benefit at 1 year to adding concentric exercise, the eccentric group had long-term improvement on the Victorian Institute of Sports Assessment-Achilles (VISA-A) questionnaire (range, 0-100; higher score indicates higher function) from a mean (SD) of 60.7 (17.1) at baseline to 89.4 (13.0) at 1 year of follow-up ( P <.001) . The MCID for the VISA-A is 7.37 (95% CI, 4.58-10.2) at 1 year …”
Section: Discussionmentioning
confidence: 96%
“…58 The MCID for the VISA-A is 7.37 (95% CI, 4.58-10.2) at 1 year. 62 In a systematic review, Scott et al 63 found that functional improvement (AOFAS hindfoot score) with ankle joint dorsiflexion night splinting or a brace with dual bladders that apply pulsatile compression to the Achilles tendon with walking was similar to eccentric training. These treatment options may be of use in patients who are unable to do eccentric training.…”
Section: Treatmentmentioning
confidence: 99%
“…A recurrence was determined after 1 year of follow-up posttreatment. We defined a recurrence either as: (1) the presence of AT pain and reduced function due to mid-AT symptoms (yes/ no), combined with a decrease in post-treatment VISA-A score of at least the minimal important change (MIC) of 7 points, as assessed for this particular cohort, 21 or (2) a self-reported recurrent episode in the past year, from which the participant was recovered at follow-up.…”
Section: Recurrence Of Mid-atmentioning
confidence: 99%
“…25 Finally, in defining a mid-AT recurrence, we used a population-specific VISA-A MIC of 7 points, as recently assessed for this particular cohort. 21 With regard to the definition of a mid-AT recurrence, several methodological choices made in the present study have to be taken into account. First, we cannot rule out that individuals defined as recovered in our study experienced a mid-AT recurrence beyond the 1-year follow-up period.…”
Section: Strengths and Limitationsmentioning
confidence: 99%